Receptor sizes and its effect on lightning protection of modern wind turbines - Ikhazuangbe, Godson I.; Kasim Rawthar, Mumtaj Begam; Gomes, Chandima; Shanmugam, Anandan (River Publishers, 2017)
Wind turbine can be destroyed when not adequately protected by the receptor. According to recent research, the size of the receptor plays a very important role in its efficiency. The effect of receptor size has not been well considered in literature and standards. This paper investigates six receptor sizes (10 mm, 15 mm, 20 mm, 25 mm, 30mmand 35mmreceptor diameters), encompassing adopted sizes in literature. As the blade is rotated, the interception efficiency of various receptor sizes is evaluated on a modern wind turbine. The vertical tri-pole cloud charge model developed with finite element analysis is used to study the maximum electric field strength required for the initiation of upward leader from the blade surfaces. The interception efficiency of each receptor size is evaluated by comparing the maximum electric field strength. The results of the point of initiation of upward leader match well with those obtained by experimental measurements from lightning discharge attachments.